Perception and Attitude of Patients Towards Waiting Time and Quality in Out Patient Department - Thakuri, Muna Malla; Shrestha, Raji (International Journal of Atharva, 2024)
Study investigates the perceptions and attitudes of patients regarding waiting times in outpatient departments (OPD) within Kathmandu Valley. Utilizing a descriptive and cross-sectional study design, data were collected from 159 respondents through a structured online questionnaire using a 5-point Likert scale. The demographic analysis revealed a predominantly young, female, and educated patient population. Descriptive analysis of patient perceptions towards OPD waiting times showed mixed satisfaction levels, with a significant number of respondents expressing neutrality or frustration. Attitudes towards the quality of care were generally positive, particularly concerning diagnosis explanation and healthcare provider friendliness. Pearson’s correlation analysis demonstrated very low, but generally positive, relationships between demographic characteristics and both perception of waiting times and attitude towards quality of care. Interestingly, occupation showed a significant, albeit low, negative correlation with satisfaction regarding waiting times. The findings suggest that while demographic factors have minimal impact, other elements of the healthcare system play a more significant role in shaping patient experiences.